Real-time audio spectrum analyser research, design, development and implementation using the 32 bit ARMR Cortex-M4 microcontroller - Just, Stefan Antonio (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2017)
This thesis describes the design and testing of a low-cost hand-held real-time audio analyser (RTAA). This includes the design of an embedded system, the development of the firmware executed by the embedded system, and the implementation of a real-time signal processing algorithms. One of the objectives of this project was to design an alternative low-cost audio analyser to the current commercially available solutions. The device was tested with the audio standard test signal (pink noise) and was compared to the expected at-spectrum response corresponding to a balanced audio system. The design makes use of an 32-bit Reduced Instruction Set Computer (RISC) processor core (ARM Cortex-M4), namely the STM32F4 family of microcontrollers. Due to the pin compatibility of the microcontroller (designed and manufactured by STMicroelectronics), the new development board can also be upgraded with the newly released Cortex-M7 microcontroller, namely the STM32F7 family of microcontrollers. Moreover, the low-cost hardware design features 256kB Random Access Memory (RAM); on-board Micro-Electro-Mechanical System (MEMS) microphone; on-chip 12-bit Analogue-to-Digital (A/D) and Digital-to-Analogue (D/A) Converters; 3.2" Thin-Film-Transistor Liquid-Crystal Display (TFT-LCD) with a resistive touch screen sensor and SD-Card Socket. Furthermore, two additional expansion modules were designed and can extend the functionality of the designed real-time audio analyser. Firstly, an audio/video module featuring a professional 24-bit 192kHz sampling rate audio CODEC; balanced audio microphone input; unbalanced line output; three MEMS microphone inputs; headphone output; and a Video Graphics Array (VGA) controller allowing the display of the analysed audio spectrum on either a projector or monitor. The second expansion module features two external memories: 1MB Static Random Access Memory (SRAM) and 16MB Synchronous Dynamic Random Access Memory (SDRAM). While the two additional expansion modules were not completely utilised by the firmware presented in this thesis, upgrades of the real-time audio analyser firmware in future revisions will provide a higher performing and more accurate analysis of the audio spectrum. The full research and design process for the real-time audio analyser is discussed and both Problems and pitfalls with the final implemented design are highlighted and possible resolutions were investigated. The development costs (excluding labour) are given in the form of a bill of materials (BOM) with the total costs averaging around R1000. Moreover, the additional VGA controller could further decrease the overall costs with the removal of the TFT-LCD screen from the audio analyser and provided the external display was not included in the BOM.
Keywords: Spectrum analyzers; Sound -- Recording and reproducing -- Digital techniques; Real-time data processing